ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSITAS KONFLIK ANTARA GAJAH DENGAN MANUSIA DI KECAMATAN MANDAU DAN KECAMATAN PINGGIR KABUPATEN BENGKALIS. - Fifin Arfiana Jogasara; Zulkarnaini Zulkarnaini; Zulfan Saam (Jurnal Ilmu Lingkungan, 2012)
The research of analysis factors that affecting conflict intensity between Elephants and Humans in the sub district Mandau and Pinggir Bengkalis regency was conducted in October-Desember 2010 by using survey methods with a closed questionnaire to 100 respondents. Analysis of data used descriptive qualitative statistical and Spearman’s rankcorrelation. The results showed that the conflict between elephants with humans in villages of Pinggir and Petani relatively high. High intensity of the conflict between elephants and humans in villages of Pinggir and Petani triggered by the proximity of communities with elephant habitat (r=0.520) and minimal public participation to response Elephant conflict (r= 0.305). As for the parameters of public awareness about the habitats and species ofElephnats uninfluence significantly to the intensity of the conflict in the location of theresearch (r = - 0.118). The research recommends increasing the participation factors and people’s organizations in conflict prevention in a comprehensive, which involve reguler and sustained participation of the government through BksDA which has a function and played alarge role in the conservation of elephants that are part of natural resources.